Higher Education Students’ Perceptions of E-Learning Quality - Amer, Talal Shaban; Musawi, Ali Sharaf Al; Muhammad, Azzam Abdul-Nabi (Journal of Education and e-Learning Research, 2022)
The aim of this study was to evaluate the quality of e-learning provision at Sultan Qaboos University, Oman, from the students’ perspective. The study employed a 48-item survey comprising six domains of e-learning provision. The questionnaire was administered to a sample of 1,858 male and female students across all colleges. The results revealed that the quality of the e-learning provision in four of the domains was at an intermediate level. The results also showed statistically significant differences in the third domain (System Effectiveness) in favor of male students, whereas there were no statistically significant differences in the other domains or the overall score. The findings of the study lead to a set of recommendations that may help to contribute to the dissemination and improvement of e-learning culture in general and its quality in particular, as well as furthering its integration in the educational process.